Pulmonary arterial hypertension in a patient treated with dasatinib: a case report - Andris Skride; Matiss Sablinskis; Kristaps Sablinskis; Krista Lesina; Aivars Lejnieks; Sandra Lejniece (Journal of Medical Case Reports, 2017)
Abstract Background There have been several reports on dasatinib-induced reversible pulmonary hypertension. This is the first reported case in Latvia; the patient did not discontinue the drug after the first adverse effects in the form of pleural effusions, which we speculate led only to partial reversion of the disease. Case presentation A 67-year-old white man with chronic myelogenous leukemia was treated with the dual Src and BCR-ABL tyrosine kinase inhibitor dasatinib. After treatment with dasatinib he had multiple pleural effusions which were suspected to be caused by congestive heart failure. Later a transthoracic Doppler echocardiography and right-sided heart catheterization revealed severe pulmonary hypertension with pulmonary vascular resistance of 12 Wood units and mean pulmonary artery pressure of 53 mmHg. Computed tomography ruled out a possible pulmonary embolism; laboratory specific tests for human immunodeficiency virus, rheumatoid factor, and anti-nuclear antibodies were negative, and dasatinib-induced pulmonary arterial hypertension was diagnosed. A follow-up right-sided heart catheterization and 6-minute walk test done a month after the discontinuation of dasatinib showed significant improvement: mean pulmonary artery pressure of 34 mmHg and pulmonary vascular resistance of 4 Wood units. Conclusions Patients should always be closely monitored when using dasatinib for a prolonged time. Dasatinib-induced pulmonary hypertension may be fully reversible after the therapy is suspended, but the key factors involved are still unclear and need to be further studied.